The Effect of activators on non-banking financial service receiving behavior in developing countries: An application of artificial neural network Neural Network - Rashel, Md. Abu; Ahmed, Faruk; Haque, A. K. M. Ahasanul; Lee, Seonsu (Serials Publication Pvt Ltd, 2017)
Aim of this paper is to measure the prediction of consumers’ response level at each selected factor using the artificial neural network, and to provide proper evidence to financial managers and executive readers for evaluating and using these variables to develop non-banking finances in developing countries. Sample size of the study was 207 respondents, and 41 variables under 8 factors were used to examine whether they respond to 5-point scale with strong relationship between input neurons, hidden neurons and output neurons throughout the artificial neural network. The results showed that Comparative Capital Benefits, Cost Benefits, Branch Service Coverage, Self-efficacy and Service Quality were positively related with Service Intention, and Risk was negatively related with Service Intention towards non-banking financial services. Finally, consumers’ attitude towards non-banking financial services positively influenced Service Behavior.